2021
DOI: 10.1186/s12889-021-11835-0
|View full text |Cite
|
Sign up to set email alerts
|

Serodiscordance predictors among couples in the HIV context: implications for health care

Abstract: Background After HIV diagnosis, people maintain, reestablish their sexual lives, or build new relationships, often with HIV seronegative partners. Therefore, understanding the factors concerning couple-vulnerability is essential in order to design effective HIV preventive strategies. We examined HIV serodiscordant couples prevalence and their associated factors from a Brazilian city. Methods This is a cross-sectional analytical study carried out wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
2
4
0
1
Order By: Relevance
“…This indicated that low CD4 count show high viral load in serum which directly facilitate high transmission rate from infected individual to uninfected one. This finding is in line with different studies [ 11 , 39 42 ]. Another study conducted in Brazil supported this finding indicating that being HIV detectable viral load will decrease the chance of being serodiscordant [ 42 ].…”
Section: Discussionsupporting
confidence: 94%
“…This indicated that low CD4 count show high viral load in serum which directly facilitate high transmission rate from infected individual to uninfected one. This finding is in line with different studies [ 11 , 39 42 ]. Another study conducted in Brazil supported this finding indicating that being HIV detectable viral load will decrease the chance of being serodiscordant [ 42 ].…”
Section: Discussionsupporting
confidence: 94%
“…These findings concur with those of a study conducted in South Africa by Madiba, Ralebona, and Lowane ( 2021 ), who posit that disclosure to family and friends about one’s HIV status is usually deliberate, selective, and often planned, where PLWHIV tend to weigh the risks and benefits associated this planned disclosure. Related to this, study findings by Antonini et al ( 2021 ) emphasise the importance of professional counselling and psycho-social support in assisting couples to cope with HIV-discordance and related disclosure.…”
Section: Discussionmentioning
confidence: 92%
“…This was a cross-sectional study carried out in health care referral units for treatment of infectious diseases in a city in southeast Brazil. The method of this study was described previously ( Antonini et al, 2021 ; Sousa et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The sample size of the study was initially calculated to estimate the prevalence of people with active sex life living with HIV in the city ( n = 10,000), considering an expected prevalence of 62% ( Antonini et al, 2021 ; Sousa et al, 2021 ). A prevalence study with a precision estimate of 0.05 and 95% confidence interval (CI) would result in a sample size of 339 participants.…”
Section: Methodsmentioning
confidence: 99%